Free large sized intra-abdominal endometrioma in a postmenopausal woman: a case report - Antoine Naem; Anwar Shamandi; Ali Al-Shiekh; Bayan Alsaid (BMC, 2020)
Abstract Background Endometriosis is an estrogen-dependent disease defined by the presence of endometrial glands and stroma out of the uterine cavity. Its prevalence is estimated to be 2-10% in reproductive aged women. Endometriosis occurrence is estimated to be 2.55% in postmenopausal patients due to the decreased levels of estrogen. Endometriosis can present in three different forms: superficial peritoneal implants, ovarian endometriomas, and deep infiltrating endometriosis. Ovarian endometriomas are the most common form of endometriosis. Even though endometriomas have been encountered in various localizations, a free abdominal endometrioma was only reported once in a premenopausal patient. Here, we are reporting the first case of a free large endometrioma in a postmenopausal patient. Case presentation A 67-year-old woman presented to the emergency department at our university hospital complaining of constipation and right flank pain. She suffered from uncontrolled primary hypertension and type 2 diabetes mellitus. On presentation, she was afebrile, hypertensive, and tachycardic. An abdominal CT scan revealed a large cystic mass measuring 17 × 26 cm in the anterior-posterior and transverse diameters respectively. The cyst caused bowel obstruction and right sided hydronephrosis. The patient underwent laparotomy and during the surgical exploration a large abdominal cyst adhered to the greater omentum was found. The cyst received plenteous blood supply from the greater omentum. The uterus and both ovaries were completely normal and didn't have any connection to the cyst. An en-bloc cystectomy was performed successfully. The final histopathology report confirmed an abdominal endometrioma. The patient had an uneventful postoperative recovery. Conclusions Endometriomas might reach large sizes regardless of their location or the patient's age. The close relation of free abdominal endometriomas with the greater omentum suggests that these were developed from endometriotic omental implants. Endometrioma is rare in postmenopausal women. However, it should be considered as a possible differential diagnosis at any age.